Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Algebra problem help!?
Please explain how you got your answer and include all the steps so I can properly understand it. Thank you.
2x - 3(-2x + 4) = -13 + x
I have plugged -1/7 into the equation about 3 times now and calculated it and they come out unequal each time.
Never mind I got it! thanks for the help.
2 Answers
- taismithLv 71 decade agoFavorite Answer
2x - 3(-2x + 4) = -13 + x
So now you want to get rid of the brackets so you multiply each of the items in the bracket with -3
2x + 6x - 12 = -13 + x
Now you want all the x on the same side and just the numbers on the other
2x + 6x - x = -13 + 12
7x = -1
Now you divide both sides by 7
x = -1/7
And you put -1/7 for each x and see if your answer is correct.
- SaraLv 41 decade ago
you have to first multiply the -3 by the two in ( ). so now you have
2x +6x - 12 = -13 + x now you add the x's together and all the numbers. so now you have:
8x -12 = -13 +x and then you move all the x's to one side and all the numbers to the other
8x - x = 7x and -13 + 12 = -1 so now oyu have 7x=-1 divide 7 from both sides to get
x = - 1/7